INOVASI AMPAS KELAPA SEBAGAI TEPUNG KUE SERBAGUNA INNOVATION OF COCONUT DRUGS AS MULTIPURPOSE CAKE FLOUR - Azis, Rosdiani; Engelen, Adnan; Mateka, Risna; Djamalu, Andrian; Mutsyahidan, Arif Murtaqi Akhmad; Modjo, Ardiyanto Saleh (Jambura Journal of Food Technology, 2024)
Coconut pulp is a by-product of the production of coconut milk. This agricultural waste is available in large quantities and has not been used optimally by the community. Crude fiber contained in young coconut fruit is digested, so it can be used as a food additive. The purpose of this study was to determine the quality characteristics of making cake flour made from coconut dregs with the addition of pandan leaf extract which will be analyzed for moisture content, ash content, color and organoleptic tests. The average value of the water content test in coconut dregs flour without pandan extract is 6,38% and with the addition of pandan extract 6,84% while the ash content of flour without the addition of pandan extract is 7,17% and with the addition of extract. Pandanus 6,71%. While the color test on flour without the addition of extract. Pandan shows a brown color while the addition of pandan extract shows a yellowish green color. Water content and ash content still meet the standard of SNI flour.